Purification and Characterization of a Fibrinolytic Enzyme from Snake Venom of Macrovipera lebetina turanica ( - Kwon Ki-Rok; Park Do-Il; Lee Seung-Bae; Choi Suk-Ho (Korean Pharmacopuncture Institute, 2011)
Objectives: Fibrinolytic enzyme preparations were isolated from the snake venom of Macrovipera lebetica turanica in this study. Methods: The purity of the preparations was determined using SDS-PAGE and the enzymic characteristics of the purified fibrinolytic enzyme were determined. Results: 1. All of the two preparations with fibrinolytic activity obtained from the snake venom of M. l. turanicat contained the major polypeptide with the molecular weight of 27,500. One of the preparation showed purified fibrinolytic enzyme. 2. The purified fibrinolytic enzyme hydrolyzed α-chain of fibrinogen faster than β-chain but not γ-chain. 3. The fibrinolytic activity was inhibited completely by EDTA, EGTA, 1,10-phenanthroline, and dithiothreitol. 4. The fibrinolytic activity was inhibited completely by calcium chloride, iron(III) chloride, mercuric chloride, and cobalt (II) chloride. 5. The fibrinolysis zone formed after addition of zinc sulfate was smaller but clearer than the control. Conclusions: These results suggested that the fibrinolytic enzyme purifed from the snake venom of M. l turanica was a metalloprotease containing dithiol group.